Hankey's clinical neurology - Gorelick, Philip B.; Testai, Fernando D.; Hankey, Graeme J.; Wardlaw, Joanna M. (CRC Press, 2014)
The second editon of Clinical Neurology has been extensively updated. This comprehensive reference guide is practical and patient-oriented. It contains clearly structured text integrating presentation, pathology, radiology, diagnosis and treatment options, enriched by illustrations of the highest quality.